IDENTIFICATION OF THE COLOR FALSE HEARDWOOD OF FAGUS SYLVATICA L. IN THE COLOR SPACE CIE L*A*B* (Innovation in Woodworking Industry and Engineering design, 2026)
The paper presents the differences in the color of native beech wood between the false heardwood and sapwood in the color space CIE L*a*b*. The visual evaluation of the differences in the color of beech wood between the false heardwood and sapwood clearly shows that the color of the false heardwood of beech wood has a reddish-brown color with values on the coordinates L* = 67.5, a* = 12.7, b* = 20.3 compared to sappwood, the color of which is a light white-gray color with a yellowish tinge with values on the coordinates L* = 77.1, a* = 9.5, b* = 18.4. The degree of color difference at the individual coordinates of the CIE L*a*b* beech wood color space between the false heardwood and sapwood indicates the fact that while the brightness of the false heardwood relative to the sapwood is ∆L* = -9.6 smaller, the red values ∆a* = +3.2 and yellow ∆b* = +1.9 in color are higher in the false heardwood in penetration with sapwood beech wood. A comparison of the values of the standard uncertainty of the measurement of the color of the false headrwood with the values of the relative standard uncertainty of the sapwood shows that the variability of the color shades of the brown-red color of the false heardwood is greater than the variability of the sapwood beech wood.